Investigation of Cutter–Woodchip Contact Pressure in a New Biomass Comminution System - Lin, Lianshan; Lanning, David; Keiser, James R.; Qu, Jun (Frontiers in Energy Research, 2022)
A Crumbler® rotary shear system has beenwas recently developed to process fuel grade wood chips into feedstocks having more uniform particle sizes for improved flowability and higher thermochemical output yields than a traditional hammer mill. It represents a significant innovation in the state of the art of biomass comminution equipment. However, the milling unit has experienced significant abrasive wear of the feeding teeth and cutters, especially when processing hard and dusty feedstocks, such as logging residue and corn stover. Here we present initial simulation results from a finite-element stress analysis of the rotary shear, which was used to investigate the dynamics of interaction between the cutters and woodchips. This is the first step for optimizing the cutter design. Along with other technical enhancements, the project goal is to improve the system lifetime and processing efficiency, thus reducing downtime and improving overall productivity.